HANR Enhances Autophagy-Associated Sorafenib Resistance Through miR-29b/ATG9A Axis in Hepatocellular Carcinoma - Shi, Yang (Onco Targets Ther, 2020)
BACKGROUND: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide and chemoresistance is the main obstacle for effective treatments of HCC. Accumulating studies indicated that long non-coding RNAs (lncRNAs) contribute to the chemoresistance of human carcinoma. However, the functional role of HANR in autophagy-mediated chemoresistance of HCC is unknown. METHODS: The expressions of HANR, miR-29b and ATG9A in tissues and cell lines were detected by real-time quantitative PCR (RT-qPCR). The expression of autophagy-related protein LC3-I and LC3-II was evaluated by Western blotting. The cell viability and apoptosis were examined by CCK-8 and flow cytometry, respectively. Bioinformatics analysis and luciferase activity assay were applied to determine the downstream target gene of HANR or miR-29b. Xenograft experiment was used to detect the effect of HANR on tumor growth. RESULTS: In the present study, we demonstrated that HANR was notably overexpressed in sorafenib-resistant HepG2 (HepG2/sora) and sorafenib-resistant Huh7 (Huh7/sora) cells, and HANR enhanced sorafenib resistance by facilitating autophagy in HepG2/sora and Huh7/sora cells. Furthermore, we demonstrated that miR‑29b could directly interact with HANR and abolished HANR-induced sorafenib resistance by suppressing autophagy in HepG2/sora and Huh7/sora cells. Moreover, ATG9A was validated as a target of miR-29b and its overexpression obviously reversed the inhibitory effect of miR-29b on sorafenib resistance and autophagy. In addition, HANR could act as a competing endogenous RNA (ceRNA) to upregulate ATG9A expression by sponging miR-29b. Hence, HANR increased autophagy-related sorafenib resistance via inhibiting the miR-29b/ATG9A axis in HepG2/sora and Huh7/sora cells, indicating that it may be a potential target to prevent chemoresistance of HCC. CONCLUSION: Our study revealed HANR enhanced sorafenib resistance by acting as an autophagy promoter by regulating miR-29b/ATG9A axis in sorafenib‑resistant HCC cells and might provide potential therapeutic strategies for HCC treatment.